THE RELATIONSHIP BETWEEN NUMERICAL ABILITY, VERBAL ABILITY, AND PEER IN SCHOOL WITH MATHEMATICS LEARNING OUTCOMES IN STUDENTS CLASS VIII OF SMP MUHAMMADIYAH 4 YOGYAKARTA - Anindita Lusiana; Aris Thobirin (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2017)
Based on the observation that has done in SMP Muhammadiyah 4 Yogyakarta that some students are less conscientious in performing basic arithmetic operations. Numeric ability, verbal ability and peer are some of the factors that relate to student learning outcomes. This research aims to know about is there any positive correlation and significance or not between manner learning, mathematics communication, and learning tools with mathematics learning outcomes in students class VIII of SMP Muhammadiyah 4 Yogyakarta in even semester in the academic year of 2016/2017. The population in this research was the students of VIII grade in SMP Muhammadiyah 4 Yogyakarta in the academic year of 2016/2017, consisted of class  VIIA, VIIIB, VIIIC, VIIID totaling 104 students. Samples were taken from VIIIB as the research sample class and with the random sampling technique. The writer uses the test method to collect the data of numeric ability, verbal ability and the resulting learning of math and questionnaire method to get peer interaction. The writer uses product-moment correlation analysis and multiple linear regression analysis to analyze the data. The results showed that there was a positive and significant relationship between manner learning, mathematics communication, and learning tools with mathematics learning outcomes in students class VIII in even Semester of SMP Muhammadiyah 4 Yogyakarta in the academic year of 2016/2017. It is showed by Fstat  Ftable is 10,491 > 3,05 with R = 0,767 and R2 = 0,5886 with , with SR , SR  and SR , SE = , SE  and SE .